Processing Presuppositions. Are Implicative Verbs Soft Triggers? - Włodarczyk, Mateusz (Research in Language, 2021)
This paper investigates the question whether implicative verbs should be considered as soft presupposition triggers, i.e., as triggers activating optional context repairs. I present the results of an experiment in which test subjects were asked to read short dialogues containing either presupposition triggers or conversational implicatures and, next, answer the questions regarding the information communicated on the level of presupposition or implicatures, respectively. The results of within-subject ANOVA show that presuppositions activated by the use of implicative verbs are significantly less accessible and illicit significantly longer response times than presuppositions activated by the use of hard triggers, suggesting that they can be classified as soft presupposition triggers. The obtained results also show that presuppositions activated by the use of different triggers are heterogenous in regards to the accessibility of information.